2001
DOI: 10.1089/089771501750055721
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Injury Is Accentuated in the Caudal Corpus Callosum of Head-Injured Patients

Abstract: Amyloid precursor protein (APP) accumulation is a sensitive marker for the axonal damage that is commonly seen in the brain as the result of head injury. This form of damage is particularly associated with midline structures such as the corpus callosum, although it is not clear whether some areas are more susceptible than others. The aim of this study was to determine if there was a differential distribution of axonal injury throughout the corpus callosum after head injury in an unselected group of cases. Coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 36 publications
5
21
0
Order By: Relevance
“…3,11,14) Injury to the corpus callosum predominantly occurs in the posterior half, particularly at the bodysplenium junction in MR imaging studies, but not in postmortem studies. 4,8,10,11,14,16,21,22) In the present study, lesions in the posterior part of the body and the splenium accounted for 56.4% of corpus callosum injuries, and 80% of lesions were located in the posterior half of the corpus callosum.…”
Section: Mechanism Of Injury To the Corpus Callosumsupporting
confidence: 46%
“…3,11,14) Injury to the corpus callosum predominantly occurs in the posterior half, particularly at the bodysplenium junction in MR imaging studies, but not in postmortem studies. 4,8,10,11,14,16,21,22) In the present study, lesions in the posterior part of the body and the splenium accounted for 56.4% of corpus callosum injuries, and 80% of lesions were located in the posterior half of the corpus callosum.…”
Section: Mechanism Of Injury To the Corpus Callosumsupporting
confidence: 46%
“…Conventional imaging and pathologic-anatomic study have indicated that the posterior corpus callosum is more susceptible to fiber disruption than the anterior corpus callosum. [2][3][4]24 In consequence, it may be hypothesized that the DTI pattern we observed in the splenium is associated with more irreversible traumatic lesions than the DTI pattern in the genu, which in turn may reflect more reversible abnormalities. This should be investigated in a longitudinal study.…”
Section: Discussionmentioning
confidence: 83%
“…It is also sometimes referred to as traumatic axonal injury (TAI)-a moniker which sidesteps the problem that this injury is not actually diffuse, but rather multifocal, with common sites of occurrence found in multiple studies. Most frequently affected are the corpus callosum and the dorsolateral part of the midbrain (e.g., LeClercq, McKenzie, Graham, & Gentleman, 2001). A tiered grading system set forth by Adams and Gennarelli and colleagues describes a grade 1 injury as affecting the hemispheric white matter, a grade 2 as having additional involvement of the corpus callosum, and a grade 3 as showing additional lesions in the superior cerebellar peduncle (Adams, Doyle, Ford, Gennarelli, Graham, & Mclellan, 1989;Gennarelli, Thibault, Adams, Graham, Thompson, & Marcincin, 1982).…”
Section: Diffuse Axonal Injury and Secondary Mechanismsmentioning
confidence: 99%